Niemieckie koncepcje rozwoju zachodniego pogranicza Polski - Kaszewska, Agnieszka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The following article deals with the involvement of Germans in the process of developing the Western Polish borderland. The discussed projects share the same feature: the lion's share of them is developed by German companies and although these projects are based on solid methodological foundations, proper regional analysis and they contain interesting suggestions concerning the course of action, they do not equally consider needs of both sides. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 159-169